2015
DOI: 10.1093/molbev/msv202
|View full text |Cite
|
Sign up to set email alerts
|

AnarchyIs a Molecular Signature of Worker Sterility in the Honey Bee

Abstract: Worker sterility is a defining characteristic of eusociality. The existence of the sterile worker caste remains a fundamental question for evolutionary biology as it requires the existence of genes that reduce personal reproduction. Currently, little is known about the proximate mechanisms underpinning worker sterility. Studies into a mutant "anarchistic" strain (in which workers can activate their ovaries) of honey bee, Apis mellifera, identified a list of candidate genes that regulate ovary activation. We qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 50 publications
3
39
0
8
Order By: Relevance
“…While kin selection theory has always had an explicit genetic focus (Hamilton 1964), researchers have made little progress in identifying specific genes that have been shaped by kin selection (Thompson et al 2013; Ronai et al 2016), or in identifying genome-wide evolutionary signatures of kin selection (Van Dyken and Wade 2012; Ostrowski et al 2015). This shortfall is particularly notable in the social insects because the sterile worker caste is the archetypical example of an altruistic phenotype that evolved through kin selection (Hamilton 1964; Queller and Strassmann 1998; Bourke 2011).…”
mentioning
confidence: 99%
“…While kin selection theory has always had an explicit genetic focus (Hamilton 1964), researchers have made little progress in identifying specific genes that have been shaped by kin selection (Thompson et al 2013; Ronai et al 2016), or in identifying genome-wide evolutionary signatures of kin selection (Van Dyken and Wade 2012; Ostrowski et al 2015). This shortfall is particularly notable in the social insects because the sterile worker caste is the archetypical example of an altruistic phenotype that evolved through kin selection (Hamilton 1964; Queller and Strassmann 1998; Bourke 2011).…”
mentioning
confidence: 99%
“…Therefore it seems that queen pheromone taps into highly conserved pathways. We have previously shown that Anarchy , a highly conserved peroxisomal membrane protein belonging to a protein family that is associated with programmed cell death (Gutiérrez‐Aguilar and Baines, ), is highly sensitive to the presence of the queen and that Anarchy 's transcripts localize to degenerating oocytes (Ronai et al ., ). Therefore Anarchy could plausibly be part of the upstream pathway that initiates programmed cell death at mid‐oogenesis in the honey bee.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, for normal development of the oocyte, programmed cell death of the nutritive nurse cells must occur in late oogenesis (Jenkins et al ., ). Histological (Tanaka and Hartfelder ; Tanaka et al ., ; Ronai et al ., ), genomic (Niu et al ., ; Ronai et al ., ) and proteomic (Cardoen et al ., ) studies of honey bee worker oogenesis indicate that programmed cell death is central to the process. In particular, we have recently found that the expression of either Anarchy or Buffy , genes that are associated with programmed cell death (Tanner et al ., ; Gutiérrez‐Aguilar and Baines ), predict the ovary state of the worker (deactivated with no mature oocytes or activated with mature oocytes) with greater than 85% accuracy (Ronai et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In sociobiology, it is common to interpret the evolution of selfless traits like sterility in terms of classical “genes for altruism” inherited in a Mendelian fashion (Ronai, Oldroyd et al, ; Thompson, Hurd, & Crespi, ). A complement to this approach involves considering both the regulation and conditional expression of such genes.…”
Section: Multigene Network For Worker Sterilitymentioning
confidence: 99%
“…Cardoen et al () found further overlap from 2D‐DIGE against the gene screens of Grozinger et al (; n = 3 genes) and Cardoen et al (; n = 31 genes), strongly suggesting that several gene‐level components of the regulatory networks are directly connected to the protein level above it. Additional studies on protein‐level interactions that mediate sterility are necessary to identify hub proteins implicated in sterility (Duncan, Hyink, & Dearden, ; Ronai, Oldroyd et al, ), caste differentiation (Begna, Han, Feng, Fang, & Li, ; Li et al, ), queen reproductive development (Pang et al, ), worker embryogenesis (Fang et al, ; Zheng et al, ), age‐dependent division of labor (Huo et al, ), and other aspects of social foraging (the proboscis extension reflex; da Silva Menegasso et al, ). Where available, information from these networks should serve to identify hub proteins and other topological features that, similarly to the gene networks, can be used to detail ideas on their origins and activity.…”
Section: Beyond Gene Networkmentioning
confidence: 99%